Zooplankton measurements, Chukchi Sea, 1976 - E. A. Pavshtiks (Arctic Data Center, 2014)
Data represents analyzed zooplankton collections from the Chukchi Sea during July and August of 1976. Samples were collected with a Juday Net with a pore opening of 168 um. Species distribution, species abundances (#/m3) and species biomass (mg/m3) are tabulated in the worksheet. Data are recovered from E.A. Pavstiks. 1984. Zooplankton of the Chukchi Sea as indices of water origins Trudy Arkticheskogo i Antarkticheskogo Nauchno-Issledovatel′skogo Institute, 368 (1984), pp. 140153 (in Russian)